Pendugaan Gen Bph1, bph2, Bph3, dan bph4 pada Galur-galur Padi Terpilih Tahan Hama Wereng Batang Cokelat (Nilaparvata lugens[Stål]) - Diani Damayanti; Dwinita W. Utami (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
Pests are major constraints to increasingrice production and brown planthoppers/BPH (Nilaparvatalugens [Stål]) is one of the major pests of rice plant.Resistance cultivar is one of the strategies for BPHmanagement. The objective of this research was to analyzethe Bph1, bph2, Bph3, and bph4 gene existence on theselected rice lines using the molecular markers. Thephenotype of the rice lines were tested based on theirresponse to BPH population collected from West Java andCental Java. Molecular markers linked to Bph1, bph2, Bph3,and bph4 were used to characterize the genotypic profilebased on PCR analysis. The results showed that there are sixgenotypes resistant to one of the BPH populations fromWest Java or Central Java. The six rice varieties weredetected to have not only allele of Bph3 gene, but also otherdifferent allele genes. B12344-2D-PN-42-1 and Inpari 13 weredetected to have the alleles of Bph3 dan Bph1 genes.B12512-18-SI-3-3-MR-3-PN-1, B12512-18-SI-3-3-MR-3-PN-1,BMIP46-4-1, and PTB33 were detected to have the alleles ofBph3 and bph2 genes. Meanwhile, B11007E-MR-3-2-PN-2-1-MR-1-2 was detected to have alleles of three genes: Bph3,bph2, and bph4. Nevertheless, this last line had mediumresistance to both BPH populations invested. There is apossibility that the interaction between two genes, Bph3 andbph4, occured which may affect the resistance responses ofrice varieties tested to BPH.